Theonellamide A, a marine-sponge-derived bicyclic peptide, binds to cholesterol in aqueous DMSO: Solution NMR-based analysis of peptide-sterol interactions using hydroxylated sterol - Cornelio, Kimberly (Animo Repository, 2019)
© 2018 Elsevier B.V. Theonellamides (TNMs) are antifungal and cytotoxic bicyclic dodecapeptides isolated from the marine sponge Theonella sp. The inclusion of cholesterol (Chol) or ergosterol in the phosphatidylcholine membrane is known to significantly enhance the membrane affinity for theonellamide A (TNM-A). We have previously revealed that TNM-A stays in a monomeric form in dimethylsulfoxide (DMSO) solvent systems, whereas the peptide forms oligomers in aqueous media. In this study, we utilized 1H NMR chemical shift changes (Δδ1H) in aqueous DMSO solution to evaluate the TNM-A/sterol interaction. Because Chol does not dissolve well in this solvent, we used 25-hydroxycholesterol (25-HC) instead, which turned out to interact with membrane-bound TNM-A in a very similar way to that of Chol. We determined the dissociation constant, KD, by NMR titration experiments and measured the chemical shift changes of TNM-A induced by 25-HC binding in the DMSO solution. Significant changes were observed for several amino acid residues in a certain area of the molecule. The results from the solution NMR experiments, together with previous findings, suggest that the TNM-Chol complex, where the hydrophobic cavity of TNM probably incorporates Chol, becomes less polar by Chol interaction, resulting in a greater accumulation of the peptide in membrane. The deeper penetration of TNM-A into the membrane interior enhances membrane disruption. We also demonstrated that hydroxylated sterols, such as 25-HC that has higher solubility in most NMR solvents than Chol, act as a versatile substitute for sterol and could be used in 1H NMR-based studies of sterol-binding peptides.